CORPORATE SOCIAL RESPONSIBILITY AS A RESERVE FOR THE GROWTH OF ENTREPRENEURIAL ACTIVITY IN THE RUSSIAN ARCTIC - Skufina, Tatiana; Bazhutova, Ekaterina; Samarina, Vera; Serova, Natalia (Humanities & Social Sciences Reviews, 2019)
Purpose of the study: To explore the consists of studying the opportunities for unlocking the potential of carrying out an entrepreneurial activity of big business within the Russian Arctic as a part of corporate social responsibility policy conducted by it. Methodology: The leading approach identified is the integrated approach which includes theoretical generalizations, analysis of practical activities of the corporations, and sociological methods of obtaining the information. Main Findings: The main concepts of big business management that contribute to boosting its entrepreneurial activity have been discussed, and opportunities for enhancing the entrepreneurial activity of big business within the Russian Arctic as a constituent of the corporate social responsibility policy have been found. Applications of this study: The materials of the paper are of practical importance for corporations working within the Russian Arctic. Novelty/Originality of this study: In the work, models of corporate social responsibility implemented by corporations of the Arctic states have been summarized.